2021
DOI: 10.1523/jneurosci.0241-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

A Preferential Role for Ventromedial Prefrontal Cortex in Assessing “the Value of the Whole” in Multiattribute Object Evaluation

Abstract: Everyday decision-making commonly involves assigning values to complex objects with multiple value-relevant attributes. Drawing on object recognition theories, we hypothesized two routes to multiattribute evaluation: assessing the value of the whole object based on holistic attribute configuration or summing individual attribute values. In two samples of healthy human male and female participants undergoing eye tracking and functional magnetic resonance imaging (fMRI) while evaluating novel pseudo objects, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Decisions are based on value, often simplified to appear as a number on a common scale, the underlying space being a simple straight line with Euclidian distance [9]. While this concept has been very fruitful, it cannot easily explain the distinction between liking and wanting for instance, or how value is built from both internal [10] and external [11] information. Altogether, it appears that while we are beginning to get a glimpse of the dimensions of subjective experience, this view is only partial given that most dimensions are preselected and differ depending on the domain, and indirect given that these dimensions are revealed through specific tasks.…”
mentioning
confidence: 99%
“…Decisions are based on value, often simplified to appear as a number on a common scale, the underlying space being a simple straight line with Euclidian distance [9]. While this concept has been very fruitful, it cannot easily explain the distinction between liking and wanting for instance, or how value is built from both internal [10] and external [11] information. Altogether, it appears that while we are beginning to get a glimpse of the dimensions of subjective experience, this view is only partial given that most dimensions are preselected and differ depending on the domain, and indirect given that these dimensions are revealed through specific tasks.…”
mentioning
confidence: 99%
“…Among the few studies involving bundles, the VMPFC has been associated with the ability to make consistent choices between bundles (Camille et al, 2011 ) and the MOFC has been shown to reflect the difference in subjective value between monetary options and bundled options (FitzGerald et al, 2009 ). In other forms of complex options, such as multi‐attribute options, activity in the VMPFC reflected also the value of the combined items (Kahnt et al, 2011 ; Pelletier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…difference in subjective value between monetary options and bundled options (FitzGerald et al, 2009). In other forms of complex options, such as multi-attribute options, activity in the VMPFC reflected also the value of the combined items (Kahnt et al, 2011;Pelletier et al, 2021).…”
mentioning
confidence: 99%
“…At the core of economic decision making lies the fundamental principle of maximizing subjective value, or utility-essentially, getting the most out of our choices [1]. A central question in neuroeconomics is precisely where this subjective value is represented in the brain [41][42][43][44][45][46][47][48][49][50][51][52] (Figure 1). Main cerebral areas related to subjective value in decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fMRI can play a key role in bridging the gap between subjective experience and decision making in neuroeconomics. By measuring brain activity indirectly through blood oxygen levels, fMRI allows researchers to pinpoint which regions are activated during economic decisions [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. This offers valuable insights into the neural basis of subjective value, helping us understand how our personal experiences, emotions, and expectations influence the choices we make.…”
Section: Decision Making Subjective Value and Fmrimentioning
confidence: 99%